Quality of nursing work life dengan kejadian burnout perawat di instalasi rawat intensif - Praditha, Mersya Rikhsan; Masitoh, Rohayati; Kurniasih, Yuni (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Nurses are healthcare workers who provide direct care and play a significant role in the quality of hospital services. High work demands, especially for nurses in intensive care units (ICU, HCU, NICU, and PICU), make them more susceptible to work stress and burnout. One important factor influencing burnout is the quality of nursing work life (QNWL), which encompasses work-home balance, work design, work context, and the work environment. Purpose: To determine the relationship between quality of nursing work life and nurse burnout. Method: This study used a quantitative descriptive correlation design and a cross-sectional approach. The population was nurses in the Intensive Care Unit of Panembahan Senopati Bantul Regional Hospital. A total sampling technique was used to select 47 nurses. Data were collected using a quality of nursing work life and burnout questionnaire. Analysis used the Spearman rank test. Results: The correlation coefficient was 0.105 (very weak) with a significance level of 0.481 >0.05 for the quality of nursing work life and burnout variables. Conclusion: Quality of nursing work life does not affect nurse burnout. Keywords: Burnout; Nurse; Quality Of Nursing Work Life. Pendahuluan: Perawat merupakan tenaga kesehatan yang memberikan pelayanan langsung dan berperan besar dalam kualitas layanan rumah sakit. Tuntutan kerja yang tinggi, terutama pada perawat ruang intensif seperti ICU, HCU, NICU, dan PICU, membuat mereka lebih rentan mengalami stres kerja dan burnout. Salah satu faktor penting yang berpengaruh terhadap burnout adalah quality of nursing work life (QNWL) yang mencakup keseimbangan kerja dan rumah, desain kerja, konteks kerja, dan lingkungan dunia kerja. Tujuan: Untuk mengetahui hubungan quality of nursing work life dengan kejadian burnout perawat. Metode: Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain deskriptif korelasi dan pendekatan waktu yang digunakan adalah cross-sectional. Populasi penelitian ini merupakan perawat di Instalasi Rawat Intensif RSUD Panembahan Senopati Bantul, sampel diambil dengan Teknik Total Sampling sebanyak 47 perawat. Data dikumpulkan dengan menggunakan kuesioner quality of nursing work life dan burnout. Uji analisis menggunakan spearman rank test Hasil: Nilai koefisien korelasi 0.105 (sangat lemah) dengan signifikansi sebesar 0.481 >0.05 pada variabel quality of nursing work life dan burnout. Simpulan: Quality of nursing work life tidak mempengaruhi burnout perawat. Kata Kunci: Burnout; Perawat; Quality Of Nursing Work Life.